Habitus, Ranah, dan Modal dalam Novel Jemput Terbawa Karya Pinto Anugrah Perspektif Pierre Bourdieu - Yeremia Charla; Aslan Abidin; Ridwan Ridwan (Cakrawala Indonesia, 2025)
This study aims to describe and analyze the forms of habitus, realm, and capital in the lives of the characters in the novel entitled Jemput Terbawa by Pinto Anugrah. The study was conducted using the sociology of literature theory from Pierre Bourdieu which is categorized into three concepts: first, habitus which emphasizes how individual habits are formed through social experience, then second, capital as a social resource that plays an important role in maintaining power, and third, realm as an arena of struggle for individuals and groups to gain power. This research is qualitative in nature which aims to describe the forms of habitus, realm, and capital of the characters in the novel. The data sources in this study were obtained through narrative quotations in the novel and analyzed based on the concepts of habitus, realm, and capital. The results of this study indicate that the characters have different forms and roles in habitus, realm, and capital. This is because each individual has their own mindset, habits, and actions in dealing with their social environment. Kalaya's habitus and background are in conflict with the norms and past trauma in the Lembah Pagadih realm, which results in Laya experiencing rejection from society. His efforts to raise capital were hampered by the stigma from the villagers, making his struggle for recognition even more difficult.